Macroeconomic dynamics and sustainability index reporting: An Islamic economic perspective on ASEAN markets - Bimantoro, Jonathan; Madnasir, Madnasir; Sisdianto, Ersi (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study investigates the relationship between macroeconomic variables and stock indices within the framework of Sustainability Index Reporting in selected ASEAN countries, incorporating an Islamic Economic perspective. Utilizing quantitative data from 2018 to 2022, the research employs panel data regression analysis, specifically a fixed effect model approach, to explore the impact of key economic indicators. The results indicate that GDP growth rate, population, interest rates, and exchange rates collectively have a significant effect on Sustainability Index Reporting, affirming the suitability of the regression model. Individually, the analysis reveals that GDP growth rate and exchange rates positively influence the Sustainability Index, while population and interest rates exert a negative impact. Moreover, GDP growth rate and interest rates are identified as significant factors, whereas population and exchange rates show an insignificant influence. These findings underscore the importance of macroeconomic stability in shaping sustainable financial practices in ASEAN markets, offering insights into the integration of Islamic economic principles in enhancing sustainable development and financial reporting.